Effects of the Photosystem II Inhibitors CCCP and DCMU on Hydrogen Production by the Unicellular Halotolerant Cyanobacterium Aphanothece halophytica - Sunisa Pansook; Aran Incharoensakdi; Saranya Phunpruch (The Scientific World Journal)
The unicellular halotolerant cyanobacterium Aphanothece halophytica is a potential dark fermentative producer of molecular hydrogen (H2) that produces very little H2 under illumination. One factor limiting the H2 photoproduction of this cyanobacterium is an inhibition of bidirectional hydrogenase activity by oxygen (O2) obtained from splitting water molecules via photosystem II activity. The present study aimed to investigate the effects of the photosystem II inhibitors carbonyl cyanide m-chlorophenyl hydrazone (CCCP) and 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) on H2 production of A. halophytica under light and dark conditions and on photosynthetic and respiratory activities. The results showed that A. halophytica treated with CCCP and DCMU produced H2 at three to five times the rate of untreated cells, when exposed to light. The highest H2 photoproduction rates, 2.26 ± 0.24 and 3.63 ± 0.26  μmol H2 g−1 dry weight h−1, were found in cells treated with 0.5 μM CCCP and 50 μM DCMU, respectively. Without inhibitor treatment, A. halophytica incubated in the dark showed a significant increase in H2 production compared with cells that were incubated in the light. Only CCCP treatment increased H2 production of A. halophytica during dark incubation, because CCCP functions as an uncoupling agent of oxidative phosphorylation. The highest dark fermentative H2 production rate of 39.50 ± 2.13  μmol H2 g−1 dry weight h−1 was found in cells treated with 0.5 μM CCCP after 2 h of dark incubation. Under illumination, CCCP and DCMU inhibited chlorophyll fluorescence, resulting in a low level of O2, which promoted bidirectional hydrogenase activity in A. halophytica cells. In addition, only CCCP enhanced the respiration rate, further reducing the O2 level. In contrast, DCMU reduced the respiration rate in A. halophytica.